Comparison of Transmission Loss Allocation by Proportional Sharing Principle Method and Aumann Shapley Method - K. Sarada, Mrs.; Anush Kumar, P; Sadiq Rahiman, Sd; Mohan Sai Krishna, Ch (International Journal of Engineering and Technology, 2018)
In the current scenario of the electricity market in the world the cost allocation became the thematic part and the essential usage to individual distributor and to the consumer. Allocation is nothing but a share of anything that been shared in the equal amount to the assigned terms of the quantity. Here in the power sector, losses and the respective costs have been shared among the generators and the loads. To achieve the linear nature and invariant characteristics, allocation of losses is done. To such allocation of losses there are many methods, popular methods of them named, Proportional Sharing Principle Method and Aumann-Shapley Method are compared in this paper based on loss and cost allocation, and results are verified through Mat lab platform.